Вплив фіторекультивації залізорудних відвалів на сезонні флуктуації кількісного та структурного складу угруповання стрептоміцетів - Syshchykova, О.V. (M.M. Gryshko National Botanical Garden of the NAS of Ukraine, 2012)
Are resulted the results of researches of phytorecultivation influence with the use of arboreal plants: Robinia pseudoacacia L., Pinus pallasiana D. Don. and grassy vegetation of iron-ore dumps on quantitative and structural composition of streptomycetes association. It is set that on numerical composition of amylolytic microorganisms and, in particular, streptomycetes the best indexes selected iron-ore dump with planting of Robinia pseudoacacia, that is confirmed by increase almost in 2.5 times of biodiversity of streptomycetes association on this area by comparison to other areas